(untitled) (Journal of International Studies, 2020)
The Straits of Malacca and Singapore are two of the world’s most significant international maritime chokepoints. The number of ships transiting the Straits of Malacca and Singapore has increased gradually and significantly over the period of 10 years since 2000. This scenario has enhanced the likelihood of the occurrence of maritime accidents in these Straits. This is further aggravated by the fact that the Straits themselves have many navigational hazards which may make navigation difficult. The navigational hazards in the Straits of Malacca and Singapore that could potentially endanger mariners and the adverse environmental impacts arising from a maritime accident are discussed in this paper. The remedies available to the littoral States of Malaysia, Indonesia and Singapore under the International law are identified for enhancing safe navigation. As an important shipping way for oil transportation, the Straits of Malacca and Singapore have to remain open for international shipping as the closure of the Straits would be detrimental to the global economy.